Предмет: Математика,
автор: ayratsharipov
Помогите пример сделать
Ответы
Автор ответа:
0
5(2*(-0,8)-8*0,9)-(6*0,9-3*(-0,8))=?
Ответ:
5(2*(-0,8)-8*0,9)-(6*0,9-3*(-0,8))=5(-1,6-7,2)-(5,4+2,4)=5*(-8,8)-7;8=-44-7,8=-51,8
Ответ:
5(2*(-0,8)-8*0,9)-(6*0,9-3*(-0,8))=5(-1,6-7,2)-(5,4+2,4)=5*(-8,8)-7;8=-44-7,8=-51,8
Похожие вопросы
Предмет: Геометрия,
автор: milpopszuzuzu
Предмет: Українська література,
автор: agapovamilana540
Предмет: Английский язык,
автор: bogdanafanasiev147
Предмет: Математика,
автор: vika7901
Предмет: Экономика,
автор: levinlevin